Analisis Pengaruh Keamanan Waiting Room terhadap Kenyamanan Penumpang di Bandar Udara Internasional Adi Soemarmo Boyolali - Azzahra, Maudina Salsabila; Hilal, Raden Fatchul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
High population mobility affects interest in using air transportation. In this case, not only airlines are assessed, but the existence of the airport also contributes to the views of passengers. In addition to providing facilities, the airport operator must prioritize security also. Guaranteed security can prevent things that are against the law that can reduce passenger’s comfortness. The quantitative method is applied in this research. The research data was obtained from the results of distributing questionnaires to 92 respondents who were passengers at Adi Soemarmo Boyolali International Airport. This research uses validity and reliability tests to test the instruments and hypothesis tests that involve normality test, correlation coefficient test, linearity test, and simple linear regression test. Based on the results of the study, it shows that the data is normally distributed because in the normality test the significance value is (0.20) > the significance level (0.05). The two variables in this study have a strong correlation because the correlation coefficient test has a significance value of 0.00 <0.05 and a Pearson Correlation value of 0.743. In the linearity test, the significance value of Linearity was 0.000 which was less than the significance level (0.05) and the significance value of Deviation from Linearity (0.124) was greater than (0.05), so that the two variables were declared to have a linear relationship. The simple linear regression test in this study shows that there is an effect of waiting room safety on passenger comfort of 55.2% with a significance value of 0.000 which is smaller than the significance level of 0.05 and the t count > t table. The passenger comfort variable has a value of 5.241 if the waiting room safety variable is eliminated, and the direction of influence in this study is positive. Keywords : security,waiting room, and comfortness.